Community-based tourism and peace parks benefit local communities through conservation in Southern Africa - Mearns, Kevin (Acta Academica: Critical views on society, culture and politics, 2012)
Community-based tourism is regarded as a potential driver of economic development for rural communities in close proximity to peace parks. The long-term success of peace parks in Southern Africa is only possible if local communities that live within or adjacent to peace parks receive significant benefits. Community-based tourism provides the means whereby such local communities may receive these benefits. This article establishes the spatial distribution of community-based tourism ventures in Southern Africa in relation to the proposed peace parks. A high degree of spatial association was found to exist between community-based tourism ventures and the proposed peace parks.